Mimesis as conditio humana (Itinera, 2024)
This contribution aims to review the contemporary debate on mimesis, opening perspectives of considerable topicality. Due to our very anthropological constitution, we become human beings only because we can implement processes that allow us to enter mimetic relationships with other human beings and the world around us. However, to speak of an authentic "social mimesis", the meaning of the mimetic act must not only be considered from an aesthetic point of view because mimesis is also (and perhaps above all) an anthropological concept, as already demonstrated using the term by the ancients. Thus, it is crucial to understand that the mimetic act is not a mere imitation in the sense of merely "making a copy", drawing attention to its cultural and social role through the staging of the body and the "culture of performance".
Keywords: social mimesis, mimetic learning, education, corporeity.